Social Robots for Language Learning: A Review - van den Berghe, Rianne; Verhagen, Josje; Oudgenoeg-Paz, Ora; van der Ven, Sanne; Leseman, Paul (Review of educational research, 2019)
In recent years, robots have increasingly been implemented as tutors in both first- and second-language education. The field of robot-assisted language learning (RALL) is developing rapidly. Studies have been published targeting different languages, age groups, and aspects of language and using different robots and methodologies. The present review presents an overview of the results obtained so far in RALL research and discusses the current possibilities and limitations of using social robots for first- and second-language learning. Thirty-three studies in which vocabulary, reading skills, speaking skills, grammar, and sign language were taught are discussed. Beside insights into learning gains attained in RALL situations, these studies raise more general issues regarding students 'motivation and robots 'social behavior in learning situations. This review concludes with directions for future research on the use of social robots in language education.